Financial distress, refinancing, and debt structure - Dudley, Evan; Yin, Qie Ellie (Journal of Banking & Finance, 2018)
We examine changes in debt structure when firms experience financial distress. At these points in time, firms refinance and undergo substantial changes in priority structure. Specifically, we find that firms diversify their priority structure relative to its pre-distress composition. We show, using a simple model, that these changes are the firm's optimal response to its joint liquidity and investment needs. Additional predictions on the yield spreads of bonds issued to meet the firm's liquidity needs are also supported by the data.